Specific alterations in mucosa-associated bacterial composition in ulcerative colitis (UC) patients with different degrees of inflammation - Yansheng Shang; Zhenzhen Zhai; Jiaguo Huang; Lixiang Li; Xiuli Zuo (Biotechnology & Biotechnological Equipment, 2022)
AbstractThe aim of this study is to evaluate the specific bacterial communities and alterations and to explore the method predicting the microbiological evolution tendency of ulcerative colitis (UC) patients. A total of 29 UC patients and 18 healthy subjects (HS) were enrolled. UC patients were grouped into mild, moderate and severe UC based on the Mayo Score. The bacterial types of the groups were distinctly different with each other on different classification levels. Interestingly, the bacterial composition of severe UC was distinctly different from others. The Chao and Ace indices of bacterial microbiota were significantly higher in the severe UC group. The main phyla in UC and HS were Firmicutes, Bacteroidetes and Proteobacteria. The percentage of the 3 main phyla in severe UC was lower than that in non-severe UC. Similar to the other groups, the main genera in severe UC were Bacteroides and Escherichia-Shigella. However, Parabacteroides and a type of Prevotella disappeared in the severe UC group. Some types, such as Faecalibacterium and Fusobacterium, decreased. On the contrary, the other types increased. The abundance of the putative pathogenic bacteria in mild UC, moderate UC and severe UC showed an increasing trend (9:11:115). Moreover, Bacillus, Lactococcus and Alloprevotella disappeared in UC. Parabacteroides and a type of Prevotella disappeared in severe UC. Serious dysbacteriosis and abundant putative pathogenic bacteriа are the two important features of severe UC. The percentage phyla and the abundance of putative pathogenic bacteria could be used to predict the evolution tendency.